Scoping Review: Hubungan Prematur dengan Kejadian Stunting pada Anak Usia di Bawah 5 Tahun - Diva Satrinabilla Armawan; Habib Syarif Hidayatuloh; Cice Tresnasari; Susanti Dharmmika (Bandung Conference Series: Medical Science, 2022)
Abstract. Stunting is a growth disorder in children caused by chronic or repeated malnutrition, recurring infections, inadequate psychosocial stimulation. In 2019, WHO said the prevalence of stunting was 21.3% worldwide. One of the most common causes of stunting is chronic malnutrition, which can be caused by conditions in the fetus, premature birth or stunted growth. Children under five who are born prematurely have an increased risk of stunting in the first two years of life. The purpose of this study was to determine the relationship between premature birth and stunting in children under 5 years of age. This study used the Scoping Review method, searching for articles from databases such as PubMed, SpringerLink, ScienceDirect, ProQuest, Ovid and Google Scholar using the keywords ("Premature Birth"[Mesh]) AND "Growth Disorders"[Mesh]) AND "Children, Preschool"[Mesh] in the period of 2011-2021. There was a total of 778 articles that met the inclusion criteria and a total of three articles successfully passed the critical assessment criteria. The results of the three articles show that there is a relationship between prematurity and the incidence of stunting in children under five years of age. Abstrak. Stunting adalah gangguan pertumbuhan pada anak yang disebabkan oleh kekurangan gizi kronis atau berulang, infeksi berulang, stimulasi psikososial yang tidak memadai. Pada tahun 2019, WHO mengatakan prevalensi stunting adalah 21,3% di seluruh dunia. Salah satu penyebab stunting yang paling umum adalah kekurangan gizi kronis, yang dapat disebabkan oleh kondisi saat janin, kelahiran prematur atau pertumbuhan yang terhambat. Anak balita yang terlahir prematur memiliki peningkatan risiko stunting pada dua tahun pertama kehidupannya. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kelahiran prematur dengan stunting pada anak di bawah 5 tahun. Penelitian ini menggunakan metode Scoping Review, dengan mencari artikel dari database seperti PubMed, SpringerLink, ScienceDirect, ProQuest, Ovid dan Google Scholar menggunakan kata kunci ("Kelahiran Prematur "[Mesh]) DAN "Gangguan Pertumbuhan"[Mesh]) DAN "Anak, Prasekolah"[Mesh] dalam periode tahun 2011-2021. Terdapat total 778 artikel yang memenuhi kriteria inklusi dan 3 artikel berhasil lolos kriteria penilaian kritis. Hasil dari ketiga artikel mengatakan bahwa terdapat hubungan antara prematur dengan kejadian stunting pada anak usia di bawah lima tahun.